(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the frequency of ischemic and haemorrhagic stroke in hypertensive patients presenting with stroke. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Department of Neurosciences, Divisions of Neurosurgery and Neurology at Sharif Medical and Dental College, Sharif Medical City Hospital, Lahore from August, 2017 to December, 2019. Materials and Methods: This study included eighty hypertensive patients with stroke and were analysed. The clinical and laboratory variables were statistically evaluated. All the clinical examination and analysis was done by same person. Results: Total of 80 patients, 18 (22%) patients were between 40-50 years of age and most of the patients 31 (39%) of stroke belong to 51-60 years of age. Mean age of the patients was 63.52±12.85 years. Forty eight (60%) patients were male and 32 (40%) patients were female with male to female ratio 1.5:1. Forty nine (61%) patients had ischemic stroke and 31 (39%) had haemorrhagic stroke. Conclusion: In hypertensive patients the frequency of ischemic stroke is increased than hemorrhagic stroke.